Influence of singular and dual MQL nozzles on sustainable milling of Al6061-T651 in different machining environments - Conger, Dervis Berk; Yapan, Yusuf Furkan; Emiroglu, Ugur; Uysal, Alper; Altan, Erhan (ELSEVIER SCI LTD, 2024)
Al6061-T651 alloy is widely used in the aerospace industry due to its superior properties and is a very difficult-to-cut material with high quality because of tool wear and thermal softening. This situation causes low surface quality, high cutting force, and limited tool life, as well as an increase in total consumed energy, total carbon dioxide emission, and total machining cost. Therefore, it is necessary to sustainably increase this aerospace alloy's machining performance. In the presented study, for the first time, milling performance and sustainability assessment of Al6061-T651 alloy under dry, minimum quantity lubrication (MQL), nano molybdenum disulfide (MoS2) reinforced nanofluid-assisted MQL (N-MQL) cutting conditions were investigated using the single nozzle and dual nozzles, two different MQL flow rates, and three different cutting speeds. In this context, the results of surface roughness, cutting force, feed force, cutting tool flank wear, total consumed energy, total carbon emission, and total machining cost were obtained. As the cutting speed increased, the cutting force, feed force, total consumed energy, total machining cost, and total carbon emission decreased by 12.9 %, 18 %, 7.8 %, 6 %, and 0.1 %, while the surface roughness increased by 34.9 %. In the MQL and MoS2 N-MQL cutting conditions at the same flow rate, using dual nozzles instead of a single nozzle improved machining response and sustainability indicators. In addition, increasing the flow rate improved machining performance and sustainability indicators. Using the double nozzle MoS2 N-MQL method reduced the surface roughness, cutting force, feed force, flank wear, total consumed energy, total carbon emission, and overall machining cost by 74.2 %, 63.9 %, 68.4 %, 66 %, 27.9 %, 0.4 %, and 6.39 %, respectively.
Keywords: Al6061-T651; MQL; Nanofluid; Dual nozzle; Flank wear; Sustainable machining; ALUMINUM-ALLOY; PERFORMANCE; SURFACE; NANOLUBRICATION; MACHINABILITY; LUBRICATION; MORPHOLOGY; EMISSIONS; 6061-T6; Engineering